Architectural and structural topics : wood-steel-concrete - Salvan, George Salinda (Quezon City, Philippines : JMC Press Inc., 1996)
The purpose of this book is to introduce architects and engineers to the structural design of concrete, wood and steel structure in one volume. Its production was undertaken because it was felt that much of the three structural topics has become too specialist and detailed in nature and does not offer an easily understood introduction to the subject. Simplified in its approach, this book is useful and practical guide and reference volume in design offices and a sustainable text for senior architectural and engineering students. Particular emphasiss has been placed on the logical order and completeness of the design examples. The examples are done in a step-by-step order and every step is worked our completely from first principles, atleast once. This book deals principally in the practical application of engineering principles and formulas and in the design of structural members. The derivations of the most commonly used formulas are given in order that the reader may comprehend fully why certain formulas are appropriate in the solution of specific problems. This text pulls together design of the various elements into a single reference. A large number of practical design examples are provided throughout the text. Because of their wide usage, buildings naturally form the basis of the majority of these examples.
Keywords: ARCHITECTURAL DESIGN